Analisis Kualitas Air dan Removal Efficiency Wastewater Treatment Plant (WWTP) di PT. Indonesia Power UPJP Priok Jakarata (Water Quality and Removal Efficiency Analysis of Wastewater Treatment Plant (WWTP) in PT. Indonesia Power UPJP Priok) - Siti Romadhonah; Chusnul Arif (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
PT. Indonesia Power UPJP Priok is a power generation industry that manages wastewater by a wastewater treatment plant (WWTP). Analysis of wastewater quality and removal efficiency (RE) needs to be conducted to fulfill the quality standards. This study aimed to analyze water quality and removal efficiency of WWTP. The materials used in the study was wastewater laboratory test results for 5 years. The results showed that the pH, TSS, oil and fat contents, Cl2, Cr, Cu, Fe, Zn, and phosphate in the inlet decreased after the processing at WWTP. The waste output at WWTP had fulfilled the quality standard. The highest RE unit value of WWTP for TSS, oil and fat, Cl2, Cr, Cu, Fe, Zn, and phosphate were 21.3%, 2.4%, 12.5 %, 15.6%, 7.8%, 25.7%, 5.7%, and 46.2%. WWTP RE values between years do not differ significantly. However, RE values in several years showed that WWTP units were less efficient which were showed by low RE values. WWTP units should be maintained every two years.